The Priorities of Leading Sub-Sector in The Sector of Agriculture, Forestry, and Fisheries in Economic Development in Bangka Belitung Province - Garist Sekar Tanjung; Any Suryantini; Arini Wahyu Utami (Universitas Muhammadiyah Yogyakarta, 2021)
The aim of the study is to determine the priorities of the leading sub-sector in agriculture, forestry, and fisheries on economic development in The Province of Bangka Belitung Island. The descriptive-analytical method is used to describe and explain the dynamical performance of each sub-sector. The sub-sector performance is represented by GRDP of Bangka Belitung Province and GDP of Indonesia based on constant prices in 2010 for the 2010-2020 periods. Analysis of Klassen Typology, Location Quotient (LQ), and Dynamic Location Quotient (DLQ) are conducted to determine the sub-sector and its position among other sub-sectors. The analysis results show that the plantation crop is a leading sub-sector priority for the economic development in the Bangka Belitung Province.